PENGARUH ORGANIZATIONAL CULTURE, PSYCHOLOGICAL CAPITAL, DAN PERCEIVED ORGANIZATIONAL SUPPORT TERHADAP PERFORMANCE KARYAWAN INDUSTRI MANUFAKTUR DI JABODETABEK MELALUI PERAN JOB SATISFACTION - Monica, Ellena Talenta; Gumilang, Dendi Anggi (POLITEKNIK LP3I JAKARTA, 2026)
This study aims to examine the effect of Organizational Culture (OC), Psychological Capital (PSC), and Perceived Organizational Support (POS) on Job Satisfaction (JS) and its impact on Employee Performance (EP), including the mediating role of JS. The study was conducted on manufacturing sector employees who had worked for at least 6 months and were permanent employees in the Greater Jakarta area, with a total of 175 respondents. Data analysis used the Partial Least Squares-Structural Equation Modelling (PLS-SEM) approach. The results showed that OC had a positive and significant effect on JS, as did POS. Conversely, PSC had no significant effect on JS. In addition, JS had no significant effect on EP. Mediation testing showed that JS was unable to mediate the influence of OC, PSC, or POS on EP. These findings indicate that in the manufacturing context, job satisfaction is more influenced by organizational factor but does not directly encourage improved performance. Therefore, the managerial implications of this study are that employee performance tends to be more determined by operational factors such as production targets, SOP compliance, supervision, shift systems, and technical competence, while job satisfaction is better improved through a corporate culture that provides support and a reward system for employees who successfully complete their work challenges.